The Demand for Money in Nepal: An Analysis Using Vector Error Correction Model - Neupane, Deepak (Prithvi Academic Journal, 2019)
This paper examines the demand for money in Nepal. Accordingly, time series techniques such as Unit Root Test, Co-integration test approach were conducted considering the annual data from 1975 to 2019. The results of the unit root test indicate that the variables are stationary at the first order difference. Moreover, the co-integration test state that there is co-integration among the real broad money supply, real GDP at producer price, inflation and the interest rate, after taking the logs of real broad money supply, real GDP and interest rate and taking the first difference of all the considered variables, which makes the series normal and stationary respectively. Besides the results of the CUSUM test indicate the stability of the model. The results of the VECM show that there exists the long-run causality of the determinants on the money demand function whereas, out of the considered variables, none has the short-run causality on the money demand function. Moreover, ordinary least square method was also conducted to compute the coefficient of parameters which showed that though only one, real GDP, out of three, was found to be significant, the model was found to be good fit with the value of R-squared 0.9933 stating that the 99.33 percent variation in the dependent variable is explained by the explanatory variables.